Menjaga Kesehatan Mental Remaja Pada Masa Pandemi Covid 19 - Sri Mulyani; Desi Lestari; Muhammad Habib (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
Maintaining the mental health of adolescents during the COVID 19 pandemic is a problem that must be understood by all groups, because maintaining the mental health of adolescents is one of the factors supporting the successful development of both the physical and psychological development of adolescents. Mental health is a healthy condition for an individual so that he can adjust himself by developing all the potential in himself, other people and the environment so that it can be useful for himself and the environment. This study aims to find out how to maintain the mental health of adolescents during the COVID 19 pandemic. This research is library research, data collection using the Documentation method, namely searching for data sourced from a lot of literature, both printed and electronic, which have links, and data analysis using Content Analysis method, namely analyzing the contents of the book relevant to the title. The results showed that maintaining the mental health of adolescents during the COVID-19 pandemic was being aware of self-anxiety, maintaining communication with friends, focusing on oneself, understanding feelings while remaining calm, supporting family/parents and getting closer to God. Maintaining the mental health of adolescents during the COVID 19 pandemic, it is hoped that the psychological development of adolescents will not be disturbed.